Effects of an oral and intravenous fat load on adipose tissue and forearm lipid metabolism. - Evans, K; Clark, M; Frayn, K (1999)
We have studied the fate of lipoprotein lipase (LPL)-derived fatty acids by measuring arteriovenous differences across subcutaneous adipose tissue and skeletal muscle in vivo. Six subjects were fasted overnight and were then given 40 g of triacylglycerol either orally or as an intravenous infusion over 4 h. Intracellular lipolysis (hormone-sensitive lipase action; HSL) was suppressed after both oral and intravenous fat loads (P < 0.001). Insulin, a major regulator of HSL activity, showed little change after either oral or intravenous fat load, suggesting that suppression of HSL action occurred independently of insulin. The rate of action of LPL (measured as triacylglycerol extraction) increased with both oral and intravenous fat loads in adipose tissue (P = 0.002) and skeletal muscle (P = 0.001). There was increased escape of LPL-derived fatty acids into the circulation from adipose tissue, shown by lack of reesterification of fatty acids. There was no release into the circulation of LPL-derived fatty acids from skeletal muscle. These results suggest that insulin is not essential for HSL suppression or increased triacylglycerol clearance but is important in reesterification of fatty acids in adipose tissue but not uptake by skeletal muscle, thus affecting fatty acid partitioning between adipose tissue and the circulation, postprandial nonesterified fatty acid concentrations, and hepatic very low density lipoprotein secretion.